A history of the global carbon budget. (15th January 2020) - Lahn, Bård
Abstract: The idea of a global "carbon budget"—the cumulative amount of "allowable" carbon emissions to meet a global temperature target—has become established as a central concept in climate science and policy. As a concept explicitly aimed at mediating between scientific knowledge and policymaking, the carbon budget has always been actively positioned in relation to ongoing policy debates, but the specific forms this concept has taken have varied. This article reviews key contributions to the carbon budget literature from the 1980s until today, in order to identify how scientists have positioned the concept between the worlds of science and policy. Three main shifts are identified in how the policy relevance of the carbon budget is envisaged in the scientific literature. The shifts can be related in part to developments in climate science, and in part to changes in international climate policy. The history of the carbon budget thus illustrates how science and policy interacts to shape dominant understandings of how climate change can be known and governed. This article is categorized under: Climate, History, Society, Culture > Ideas and Knowledge Abstract : The near‐linear relationship between cumulative carbon emissions and global temperature rise, as illustrated in the Intergovernmental Panel on Climate Change Special Report on 1.5°C (IPCC, 2018, p. 105).